1992
DOI: 10.1159/000168440
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Fever with Renal Syndrome in an Endemic Area of Greece

Abstract: From 1983 to 1990, 32 patients with hemorrhagic fever with renal syndrome (HFRS) were admitted to our hospital. The diagnosis was confirmed by high IgM type titers of antibodies to Hantaan virus. All patients presented with serum and urine abnormalities suggesting renal involvement. Serum creatinine was elevated and ranged between 1.8 and 14.3 mg/dl. Proteinuria ranged between 0.5 and 6.4 g/24 h. Seven patients died due to shock or hemorrhage, while 6 patients were supported by hemodialysis or peritoneal dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
2
6
1
Order By: Relevance
“…In our region, we also found that mild (flu-like syndrome) or asymptomatic cases of HFRS may be more common than the severe type of the disease and these patients are usually misdiagnosed [16, 231. In endemic areas such as ours, this hypothesis can explain the frequency of 13 % of anti-HVD antibodies in haemodialysis patients possibly due to a direct (via aspiration), symptomless infection or to transfusions from asymptomatic donors, although no association between anti-HVD positivity and transfusions were observed in our study. This finding, in association with our previous report ( [9], two out of 32 patients were discharged with some degree of renal impairment which remained stable 12-1 5 months later) as well as with recent data showing chronic renal dysfunction in surviving HFRS patients (15), suggests that HFRS in endemic areas may cause chronic renal failure (CRF). This relatively high frequency of anti-HVD antibodies in haemodialysis patients was higher than the expected frequency from endemic regions [16,231 as well as than the frequency in healthy blood donors from our area (unpublished data).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our region, we also found that mild (flu-like syndrome) or asymptomatic cases of HFRS may be more common than the severe type of the disease and these patients are usually misdiagnosed [16, 231. In endemic areas such as ours, this hypothesis can explain the frequency of 13 % of anti-HVD antibodies in haemodialysis patients possibly due to a direct (via aspiration), symptomless infection or to transfusions from asymptomatic donors, although no association between anti-HVD positivity and transfusions were observed in our study. This finding, in association with our previous report ( [9], two out of 32 patients were discharged with some degree of renal impairment which remained stable 12-1 5 months later) as well as with recent data showing chronic renal dysfunction in surviving HFRS patients (15), suggests that HFRS in endemic areas may cause chronic renal failure (CRF). This relatively high frequency of anti-HVD antibodies in haemodialysis patients was higher than the expected frequency from endemic regions [16,231 as well as than the frequency in healthy blood donors from our area (unpublished data).…”
Section: Discussionsupporting
confidence: 88%
“…In 1982 two cases of haemorrhagic fever with renal syndrome (HFRS) were serologically diagnosed in northern Greece [ 71 and in 1985 there was an outbreak in north-western Greece [8]. During the last 9 years, 32 cases have been identified in our department [9]. Hepatitis C virus (HCV, a small positive-stranded, RNA virus) is the causative agent of the majority of the post-transfusion non-A.…”
mentioning
confidence: 99%
“…It is questionable whether the viral antigen would also be found in the endothelium of small vessels in the pancreas and the degree to which the acute pancreatitis contributes to ARF in these patients. In contrast to the report of other authors (12), who evaluated a similar number of patients, the survival rate was better in our group. We suppose that very early supportive and symptomatic treatment of patients with HFRS, avoiding hypotension, may have an important role in this issue.…”
Section: Discussioncontrasting
confidence: 99%
“…We suppose that very early supportive and symptomatic treatment of patients with HFRS, avoiding hypotension, may have an important role in this issue. We agree with others (12,13,14), and our results suggest, that some patients may have chronic sequels and not complete recovery after ARF due to HFRS.…”
Section: Discussionsupporting
confidence: 93%
“…Herein, we would like to present our data on the permanent renal sequelae found in HFRS patients. During the last 10 years, 32 patients with HFRS have been diagnosed in our center [3]. Seven patients died, 23 patients were discharged healthy, while in another 2 patients some degree of renal dysfunction which remained stable 12-15 months later was evident.…”
mentioning
confidence: 99%